2011
DOI: 10.1152/japplphysiol.00575.2010
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte enzymatic antioxidant responses to oxidative stress following high-intensity interval exercise

Abstract: The purposes of this study were to 1) examine the immune and oxidative stress responses following high-intensity interval training (HIIT); 2) determine changes in antioxidant enzyme gene expression and enzyme activity in lymphocytes following HIIT; and 3) assess pre-HIIT, 3-h post-HIIT, and 24-h post-HIIT lymphocyte cell viability following hydrogen peroxide exposure in vitro. Eight recreationally active males completed three identical HIIT protocols. Blood samples were obtained at preexercise, immediately pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 39 publications
7
82
3
4
Order By: Relevance
“…This is consistent with previous reports that reported that the activities of antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GPX) and catalase (CAT) were increased in the human lymphocytes when induced by oxidative stress [29]. Another indication about the peptides in crude leukocyte extracts from C. siamensis as described by Theansungnoen et al [30], who reported the antioxidant activity was observed in two peptides i.e.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous reports that reported that the activities of antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GPX) and catalase (CAT) were increased in the human lymphocytes when induced by oxidative stress [29]. Another indication about the peptides in crude leukocyte extracts from C. siamensis as described by Theansungnoen et al [30], who reported the antioxidant activity was observed in two peptides i.e.…”
Section: Discussionsupporting
confidence: 92%
“…However, concentrations of TBARS and protein carbonyls have been repeatedly shown to consistently increase after exercise in many studies from our group and from other groups (23,31,32). In addition, it has been found that concentrations of TBARS and protein carbonyls followed similar changes to F 2 -isoprostane concentrations (nowadays considered the reference method) after chronic muscle-damaging exercise (33).…”
Section: Assayssupporting
confidence: 59%
“…Although this may be considered as a limitation of the present work, yet many studies from our and other research groups (Fisher et al 2011;Nikolaidis et al 2007Nikolaidis et al , 2008 have repeatedly shown that TBARS concentrations have been consistently increasing after exercise. In addition, it has been found that TBARS concentrations followed similar changes to F2-isoprostane concentrations (currently considered the reference method) after exercise (Margonis et al 2007).…”
Section: Comparison Of Blood Redox Status Between the Normoxemic And mentioning
confidence: 79%